Extensive role of foreign direct investment in development of Indian economy - Amit Saini; Pankaj Madan; S. K. Batra (UTMS Journal of Economics, 2016)
Since 2001, the extensive growth in domestic economy were potentially associated with the scale of foreign direct inflows that were largely interconnected with industrial growth, re-shuffling investment policies, and availability of large market size in India. However, the government remained much restrictive earlier in these issues to protect the domestic entrepreneurs along with to promote the self-efficacy among individuals. Within this framework, this paper is being prepared to observe the degree of effect of foreign direct investment inflow over successive economic parameters such as gross domestic product and Export. Moreover, to define such interconnection, the generalized linear model econometric model has been developed to analyze the overall effect and uni-variate effect over three categorical factors i.e. country, year and foreign direct investment itself. Finally, the results shown, the consistent foreign direct investment inflows is the result of successive years that led to increase the prestige of gross domestic products and Export in many folds during a period from 2000 to 2012.
Keywords: F15; F21; F35; 330; extensive growth; generalized linear mode; financial needs; policies framework; gross domestic product